(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Recent years have seen an increase in the use of boric acid [H3BO3]. Here, the most recent developments in boric acid catalysed transformations, such as esterification and transesterification are summarised, as well as the addition of azide and thiazide and the aza- and thia-Michael additions, condensation and the Friedel-Crafts and Tishenko reactions, as well as halogenations, ipso substitutions, decarboxylations, reactions of protection and deprotection, amidation and A number of biologically relevant chemical molecules have been synthesised using Boric acid as a benign, commercially available, and inexpensive catalyst in the recent decade.